Cancer Immunotherapy Based on the Bidirectional Reprogramming of the Tumor Microenvironment by a “Brakes Off/ Step on the Accelerator” Core‐Shell Manganese Phosphate/siPD‐L1 Modulator - Fei Xia; Yuqian Lu; Zipeng Gong; Qingchao Tu; Shuntao Liang; Chen Wang; HaiLu Yao; LinYing Zhong; Yuanfeng Fu; Pengbo Guo; Yichong Hou; Xinyu Zhou; et al. (Exploration)
ABSTRACT The insufficient infiltration and functional inhibition of CD8+ T cells due to tumor microenvironment (TME) are considered enormous obstacles to anti‐tumor immunotherapy. Herein, a pH‐responsive core‐shell manganese phosphate nanomodulator co‐loading siPD‐L1 and Mn2+ into nanoparticles coated with hyaluronic acid was prepared, which was aimed at the bidirectional reprogramming the tumor microenvironment: (1) “Brakes off,” restoring CD8+ T cells function by siPD‐L1 knockdowning PD‐L1 expression of tumor cells; (2) “Step on the accelerator,” promoting CD8+ T cells infiltration in tumors tissue based on the multidimensional immune effects of Mn2+ (immunogenic cell death induced the enhancing cGAS‐STING pathway, the proliferation and maturation of relative immune cells). Additionally, this strategy could induce macrophage polarization and inhibit the regulatory T cells in tumor site. This work provided a manganese phosphate nanomodulator to reprogram the immune TME for an enhanced comprehensive anti‐tumor effect of triple negative breast cancer, which offers a robust method for tumor immunotherapy in future clinical applications.